Kerjasama Kegiatan Kemahasiswaan BK2PTKI – Badan Koordinasi Kemahasiswaan Perguruan Tinggi Kristen Indonesia - Libianko Sianturi; Sindak Hutauruk; Rimbun C.D. Sidabutar; Jamser Simanjuntak (Jurnal Visi Pengabdian Kepada Masyarakat, 2022)
The purpose of this community service activity is to provide an overview, understanding and alternative forms of student collaboration that can be carried out together in the BK2PTKI – Badan Koordinasi Kemahasiswaan Perguruan Tinggi Kristen Indonesia - Indonesian Christian Higher Education Student Cooperation Agency. At the national meeting with the theme: revitalization of the student body in the era of the kampus merdeka and the sub-theme: strategy for managing student activities in the era of the kampus merdeka, the Presenter Team was given the opportunity to deliver material with the topic: "Cooperation for BK2PTKI Student Activities".  According to the topic, the Presenter Team said that there are several opportunity of collaboration and the possibility of organizing collaborations in organizing joint activities among BK2PTKI members including national competitions, national training, national student scientific meetings, national student publications and others. This collaboration is expected to produce several forms of student activity reports such as MOU documents, MoA documents, and IA documents. In addition, all of collaborations activities will produce student achievements at the national level as well as national student publications. Therefore, the collaboration that will be carried out will support many things, especially in the field of student affairs. Another advantage of this collaboration is support for the accreditation of Study Programs and Institutions, increasing the ranking of institutions at the LLdikti level and the level of the Ministry of Education as well as increasing student ratings at Simkatmawa